Mapping of adolescents with gingivitis and dental calculus - Fonseca, Emilio Prado da; Ferreira, Efigênia Ferreira; Abreu, Mauro Henrique Nogueira Guimarães; Palmier, Andréa Clemente; Vargas, Andréa Maria Duarte (Journal of Health Informatics, 2017)
Objective: The aim of this study was to map the distribution of periodontal disease in adolescents in the Jequitinhonha Valley. Methods: We constructed maps with varying Community Periodontal Index (CPI). The cities were selected based on population size and performance of oral health services. The sampling plan was composed of 450 individuals between 15 and 19 years, randomly selected in number corresponding to the proportion of the adolescent population in each municipality. Results: Of the 450 adolescents examined were 16 (3.5%) code 0 (Healthy), 232 (51.5%) of the code 1 (bleeding), 38 (8.44%) code 2 (Calculus) and 164 (36.44%) code 6 (bleeding and calculus). The pattern of mosaic maps was kind and may indicate that the worst periodontal conditions of adolescents were distributed throughout the region. Conclusion: maps described the oral health status of adolescents and can provide information for planning oral health.